2007
DOI: 10.1007/s00228-007-0329-x
|View full text |Cite
|
Sign up to set email alerts
|

Serum and cerebrospinal fluid morphine pharmacokinetics after single doses of intravenous and intramuscular morphine after hip replacement surgery

Abstract: The uptake of morphine to the CSF was consistently higher after IV administration than after IM already after 10 min. The higher CSF concentration may be caused by an initially higher morphine blood/CSF gradient following IV morphine injection. The pharmacokinetic findings are compatible with a more rapid and extensive initial effect of IV morphine compared with IM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…This may explain our finding regarding the lack of correlation between M6G plasma concentrations and morphine clinical effects in the PACU. Interestingly, after intravenous administration of 10 mg of morphine, no metabolites were detected in CSF samples after 120 min despite their rapid rise in plasma concentrations, confirming the lack of contribution of M6G to morphine-related central nervous effects during this period [37]. Our finding is in line with the failure to produce analgesia in experimental and clinical pain after administration of M6G at similar doses to those resulting from metabolism of analgesic doses of morphine [36][37][38][39].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This may explain our finding regarding the lack of correlation between M6G plasma concentrations and morphine clinical effects in the PACU. Interestingly, after intravenous administration of 10 mg of morphine, no metabolites were detected in CSF samples after 120 min despite their rapid rise in plasma concentrations, confirming the lack of contribution of M6G to morphine-related central nervous effects during this period [37]. Our finding is in line with the failure to produce analgesia in experimental and clinical pain after administration of M6G at similar doses to those resulting from metabolism of analgesic doses of morphine [36][37][38][39].…”
Section: Discussionsupporting
confidence: 82%
“…Interestingly, after intravenous administration of 10 mg of morphine, no metabolites were detected in CSF samples after 120 min despite their rapid rise in plasma concentrations, confirming the lack of contribution of M6G to morphine‐related central nervous effects during this period [37]. Our finding is in line with the failure to produce analgesia in experimental and clinical pain after administration of M6G at similar doses to those resulting from metabolism of analgesic doses of morphine [36–39]. It may be noted that another recent study in postoperative patients demonstrated the delayed role of M6G on morphine analgesia, with a significant correlation between M6G/M3G plasma concentration ratio and analgesia observed only after the fourth hour of intravenous morphine administration [40].…”
Section: Discussionmentioning
confidence: 91%
“…IV morphine has a more rapid and extensive initial effect compared with IM, which is supported by the findings of the pharmacokinetic study by Dale et al 80 Dale compared the time course of morphine and metabolite concentrations in serum and cerebrospinal fluid (CSF) after IV and IM administration of morphine 10 mg after surgery. The uptake of morphine to the CSF was consistently higher after IV administration than after IM administration.…”
Section: Resultsmentioning
confidence: 75%
“…In humans, ~44–55% of morphine is metabolized to morphine-3-glucuronide (M3G), 9–15% to morphine-6-glucuronide (M6G), 8–10% excreted as morphine and the remainder converted into numerous minor metabolites (Christrup, 1997; Andersen et al, 2003). Clinical studies have consistently found M3G and M6G in the CNS following systemic morphine, including in lumbosacral cerebrospinal fluid (CSF) (Sjogren et al, 1998; Dale et al, 2007). …”
mentioning
confidence: 99%